Generation Y and Z’s Attitude Toward Online Video Advertisement Effect on Impulsive Buying Tendency: Evidence from TikTok - Adyantari, Api (Review of Management and Entrepreneurship, 2023)
This research was carried out to examine the factors impacting the impulsive buying tendency of young consumers, focusing on Generation Y and Z, through online video advertisements on TikTok. TikTok is a growing video-sharing application that supports users to make and share a short video on any topic. This study aims to help enterprises get a better insight into their young consumers. This study utilized the Theory of Reasoned Action (TRA) to examine the relationship between informativeness, entertainment, personalization, credibility, and attitude toward online video advertisement. Also, its impacts towards users’ tendency to buy impulsively. The data were gathered from 322 young participants born from 1981 to 2022. The data was further processed statistically using SPSS and SmartPLS. The findings indicate that the informativeness, entertainment, personalization, and credibility of online video advertisements positively affect attitude toward online video ads. The more positive attitude toward online video ads, the higher the tendency to buy the advertised product impulsively. This study provides practical advice for marketers and brand managers to focus on improving consumers’ perception through the video ad’s informativeness, entertainment, personalization, and credibility to encourage consumers to purchase impulsively.